Understanding the gut microbiota and sarcopenia: a systematic review - Liu, Chaoran; Cheung, Wing‐Hoi; Li, Jie; Chow, Simon Kwoon‐Ho; Yu, Jun; Wong, Sunny Hei; Ip, Margaret; Sung, Joseph Jao Yiu; Wong, Ronald Man Yeung (Journal of cachexia, sarcopenia and muscle, 2021)
Background Gut microbiota dysbiosis and sarcopenia commonly occur in the elderly. Although the concept of the gut–muscle axis has been raised, the casual relationship is still unclear. This systematic review analyses the current evidence of gut microbiota effects on muscle/sarcopenia. Methods A systematic review was performed in PubMed, Embase, Web of Science, and The Cochrane Library databases using the keywords (microbiota* OR microbiome*) AND (sarcopen* OR muscle). Studies reporting the alterations of gut microbiota and muscle/physical performance were analysed. Results A total of 26 pre‐clinical and 10 clinical studies were included. For animal studies, three revealed age‐related changes and relationships between gut microbiota and muscle. Three studies focused on muscle characteristics of germ‐free mice. Seventy‐five per cent of eight faecal microbiota transplantation studies showed that the recipient mice successfully replicated the muscle phenotype of donors. There were positive effects on muscle from seven probiotics, two prebiotics, and short‐chain fatty acids (SCFAs). Ten studies investigated on other dietary supplements, antibiotics, exercise, and food withdrawal that affected both muscle and gut microbiota. Twelve studies explored the potential mechanisms of the gut–muscle axis. For clinical studies, 6 studies recruited 676 elderly people (72.8 ± 5.6 years, 57.8% female), while 4 studies focused on 244 young adults (29.7 ± 7.8 years, 55.4% female). The associations of gut microbiota and muscle had been shown in four observational studies. Probiotics, prebiotics, synbiotics, fermented milk, caloric restriction, and exercise in six studies displayed inconsistent effects on muscle mass, function, and gut microbiota. Conclusions Altering the gut microbiota through bacteria depletion, faecal transplantation, and various supplements was shown to directly affect muscle phenotypes. Probiotics, prebiotics, SCFAs, and bacterial products are potential novel therapies to enhance muscle mass and physical performance. Lactobacillus and Bifidobacterium strains restored age‐related muscle loss. Potential mechanisms of microbiome modulating muscle mainly include protein, energy, lipid, and glucose metabolism, inflammation level, neuromuscular junction, and mitochondrial function. The role of the gut microbiota in the development of muscle loss during aging is a crucial area that requires further studies for translation to patients.